The corporate objective : Meta-synthesis of legal, economic and managerial literatures on the shareholder value maximization as a corporate objective - Vuorinen, Vesa (My University, 2019)
Social science usually strives to maximize the social welfare and economics as a science influencing in the society should strive to maximize the social welfare in the economy. Capitalism and the corporate form of business are among the most influential innovations ever made by the humankind, simply because they determine how the scarce resources of our planet Earth are allocated. Many publicly listed corporations are governed through the shareholder value maximization theory which claims to maximize the social welfare when the shareholder value is maximized. The question that remains unanswered is how social welfare becomes maximized when the shareholder value becomes maximized and why the scholars and practitioners are unable to conclude what should be the corporate objective? Articles from six major databases are systematically collected and reviewed to examine the viability of the shareholder value maximization as a corporate objective. In total of 68 articles were systematically retrieved. Theoretical sampling is employed to elaborate the depth and quality of the synthesis. The goal is to introduce ideas, historical pathways, logics, inconsistencies and misunderstandings to provoke further investigation and discussion. The central objective of the thesis is to either justify the shareholder value maximization as a corporate objective or to refute its position as such. Results suggest that all existing arguments for the shareholder value maximization can be either deduced to the utilitarian logic or dismissed as irrelevant. The only viable justification for the corporate objective is that it increases social welfare in the utilitarian sense. The thesis provides a timeline and synthesizing graphical presentation of the typology of the shareholder value maximization. The typology and the timeline are unprecedented contributions. The timeline helps to connect different data points to the shareholder value maximization. The overarching conclusion is that market failures and externalities are significantly weakening the possibilities of the shareholder value maximization to successfully maximize the social welfare. However, shareholder value maximization might still be the best alternative providing the closest approximate of the maximum social welfare.
Keywords: Shareholder value maximization; corporate objective; corporate governance; agency theory; stakeholder; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development